Comportamento mecânico, funcional e ambiental de misturas asfálticas porosas - Alves, Alessandro (2019)
Road transportation is the main means of transportation in Brazil and it is also known that about 90% of paved roads have asphalt concrete as a coating layer. When it comes to OGFC (Open-Graded Friction Course) hot mixtures, it is understood that they are designed with void percentages of 18% to 25% and used as a wearing course over asphalt coatings. Their initial and well-known objective was to promote surface drainage of water on rainy days by mobilizing its percolation to drainage gutters. However this coating has also been studied due to its behavior regarding noise reduction. Traffic noise results from the accumulation of noise emissions from all vehicles, although coming from various sources that result from the sum of engine operation, exhaust system and tire/road interaction. The first two sources of noise occur mainly at low speeds, while at speeds above 40 km/h the noise of tire/pavement interaction is predominant. Environmental noise is one of the main factors that harm health, being the second largest cause of disease, second only to air pollution. Quiet pavements are an alternative to attenuate noise generation and propagation. The main objective of this study is to develop a mechanical, functional and environmental assessment, focusing on the acoustics of OGFC. The methodology used in the laboratory experiments follows the procedures defined by the standards for the tests of: tensile strength, resilience modulus, cantabro wear, hydraulic conductivity, communicating voids, uniaxial and triaxial repeated load test, uniaxial dynamic modulus and the coefficient of acoustic absorption through the impedance tube. These were performed based on a sampling plan in order to evaluate the mechanical and functional behavior of open-graded mixtures. SPL (Sound Pressure Level) measurements were made by the statistical pass-by method and also SPL assessments regarding octave bands and dry track vs. wet track variation. Also on-site checks were made for WTR (Wheel Track Rutting), IRI (International Roughness Index), macrotexture, microtexture and drainability. It can be verified from the assessments in the OGFC pavements of this work, that its behavior related to noise reduction over time remains constant, with reductions close to 6 dB (A), similar to the silent pavements used worldwide. In an analysis linked to the rutting, the OGFC presented deformations smaller than 7mm (limit for the National Land Transportation Agency - ANTT) even for sections with more than 15 years of opening to traffic, demonstrating its good behavior also in relation to this parameter.